Effect of bacillus subtilus on sow and baby pig performance and bacterial populations - LaForge, R.R.; Pollmann, D.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A Bacillus subtilus probiotic was tested using a total of 52 sows and 516 baby pigs to determine the effect on enteric colibacillosis control and on host bacterial population. The probiotic did not affect sow or baby pig performance nor influence host bacterial populations of the digestive tract.
Keywords: Swine; Bacillus subtilus; Baby pig performance; Bacterial populations